Differences in Subject-Specific Competences between Slovenian and Italian Physical Education Teachers - Marjeta Kovac; Bojan Leskosek; Gregor Jurak; Miha Marinsek; Milos Tul (Montenegrin Sports Academy, 2021)
This cross-sectional study was designed to analyse the differences between the subject-specific competenc- es of Slovenian and Italian physical education (PE) teachers. The participants, 669 Slovenian and 484 Italian PE teachers, evaluated their professional competences with a self-administered questionnaire on a four-level Likert scale. A t-test for independent samples indicates differences in the self-evaluations of the majority of sub- ject-specific competences between both groups. However, in almost all items, Slovenian PE teachers evaluate their competences higher. A multivariate analysis of variance, used to identify the role of some socio-demo- graphic factors (state, gender, years of service), shows that the state has the highest impact on the differences between self-efficiency of both groups (p<0.001, Eta2=0.531). The greatest differences (Cohen's d > 0.8) are observed on those competences that relate to some of the narrower aspects of PE didactics. The reasons for the perceived differences can be found in some historical and social events, length of education, the different orientation of PE teacher education programmes, and the different responses of both countries to educational policies. The present study outcomes may aid in updating initial PE teacher training and designing a creative system of continuous professional development.